Answer:
y = -2x + 5 [ 1st option ]
Step-by-step explanation:
Consider any two points , say
Firstly let's find the slope of the line as ,
=> m = y₁ - y₂ / x₁ - x₂
=> m = 3-1 / 1-2
=> m = 2/-1
=> m = -2
Third point is, (3 , -1) . Using slope point form .
=> y - y₁ = m ( x - x₁ )
=> y - (-1) = -2( x - 3)
=> y + 1 = -2x +6
=> y +2x +1-6=0
=> y +2x -5 = 0
=> y = -2x + 5
On looking at options first one is correct
<h3><u>Hence</u><u> the</u><u> </u><u>equation</u><u> of</u><u> line</u><u> </u><u>is </u><u>y </u><u>=</u><u> </u><u>-2x </u><u>+</u><u> </u><u>5</u><u>.</u></h3>